2008
DOI: 10.1016/j.jmb.2007.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Equilibria and Rates of Localized Motion within Hepatitis B Virus Capsids

Abstract: Functional analysis of Hepatitis B virus (HBV) core particles has associated a number of biological roles with the C-terminus of the capsid protein. One set of functions require the C-terminus to be on the exterior of the capsid, while others place this domain on the interior. According to the crystal structure of the capsid, this segment is strictly internal to the capsid shell and buried at a proteinprotein interface. Using kinetic hydrolysis, a form of protease digestion assayed by SDS-PAGE and mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
61
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 81 publications
16
61
0
1
Order By: Relevance
“…7), in mature NC formation/ integrity suggests that maturation-associated NC structural changes, perhaps triggered by the altered interactions of HBc with the dsDNA in mature NCs versus the ssDNA or pgRNA in immature NCs (52), may be initiated and/or propagated through the dimer interface. Interestingly, a previous study indicated that the neighboring R127 is susceptible to protease digestion in the context of recombinant capsids as a consequence of dynamic local unfolding and refolding (53), consistent with an important role of this region in the structural dynamics of NC during maturation. L60 is located at the base of the spike on the capsid surface, and our results suggest that this location is also involved in regulating NC integrity associated with NC maturation.…”
Section: Discussionsupporting
confidence: 66%
“…7), in mature NC formation/ integrity suggests that maturation-associated NC structural changes, perhaps triggered by the altered interactions of HBc with the dsDNA in mature NCs versus the ssDNA or pgRNA in immature NCs (52), may be initiated and/or propagated through the dimer interface. Interestingly, a previous study indicated that the neighboring R127 is susceptible to protease digestion in the context of recombinant capsids as a consequence of dynamic local unfolding and refolding (53), consistent with an important role of this region in the structural dynamics of NC during maturation. L60 is located at the base of the spike on the capsid surface, and our results suggest that this location is also involved in regulating NC integrity associated with NC maturation.…”
Section: Discussionsupporting
confidence: 66%
“…Slowly, it became evident that in addition to structure, dynamics is an integral part of VP function (16,40,71,72,75,(78)(79)(80)(81)(82). This study focused on characterizing the solution phase properties of four AAV serotypes for which high-resolution structures are available.…”
Section: Discussionmentioning
confidence: 99%
“…5 show that subtle differences in the dynamic regions exist between capsids. AAV1 and AAV2 are more rapidly digested, based on the rate of VP3 hydrolysis, indicating that they may be more dynamic than AAV5 and AAV8 (72,73). While it is perhaps intuitive that there should be a correlation between thermal stability and limited conformational freedom, this is not required by thermodynamics or kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that HAP12 altered the dynamics of the assembled capsids. HBV capsids are highly dynamic, opening and closing on a scale of seconds (43), which could certainly affect the elution volume. V124W mutant dynamics and its response to HAPs have not yet been investigated, and other explanations cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%